The ‘MOAHLFA(P) Index’: An Attempt to Standardise a Widely Used Array of Descriptors of Patch-Tested Patients - Uter, Wolfgang; Andersen, Klaus Ejner; Brans, Richard; Bruze, Magnus; Schubert, Steffen; Gonçalo, Margarida; Aalto-Korte, Kristiina; Aerts, Olivier; Agner, Tove; Bircher, Andreas; Bonefeld, Charlotte Menne; Brans, Richard; et al. (Contact Dermatitis, 2025)
Background: Since its inception in 1980, the MOHL index (% patients who are male, have occupational, hand, or leg dermatitis, respectively) and its later evolutions until the presently used MOAHLFA(P) index (adding % patients with atopic dermatitis, face dermatitis, age 40+ years and positive reaction(s) to ≥ 1 baseline series allergen) have been intended to convey important demographic and clinical information on the patients patch tested in a certain area and time, aiding the interpretation of the observed spectrum of sensitisation. Objectives: To examine the current usage of the MOAHLFA(P) index and suggest consolidated definitions for its single items. Methods: A title/abstract search in Medline identified publications mentioning the evolving acronyms. A Delphi-like survey among contact dermatitis experts collected agreement with suggested definitions. Results: The search term ‘MOAHLFA’ was used in 35 publications from a broad geographical origin. More than 80% of the 24 participants of the survey (65% response) agreed on maintaining to use (i) sex for the ‘M’ criterion, (ii) occupation-related dermatitis irrespective of medicolegal definitions for the ‘O’, (iii) atopic dermatitis (but not rhinitis or asthma) for the ‘A’. The possibility to use more than one site among ‘H’, ‘L’ and ‘F’ and a more detailed description of age distribution were favoured, and the difficult interpretability of the ‘P’ measure was highlighted. Conclusions: The ‘classical’ MOAHLFA(P) index may be extended. Some aspects, notably atopic dermatitis, need further standardisation.
CRIS-Team Scopus Importer:2025-01-31
Keywords: clinical epidemiology; contact dermatitis; patch testing